The method of fixation of the ulnar nerve after its subcutaneous transposition - Goloborod’ko, Sergey (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
For prevention of dislocation of the ulnar nerve after its subcutaneous transposition they use various methods: fixation of the nerve with cut in a special way fascial or adiposal patches-blocks. The paper presents one more way to solve this problem. Objective: To describe the method of fixation of the ulnar nerve after its subcutaneous transposition. The method is simpler and less traumatic compared with other ones. Methods: subcutaneous transposition of the ulnar nerve we performed in 8 patients with idiopathic syndrome of cubital channel and in 3 with inveterate injury of the ulnar nerve. For approach to the ulnar nerve in the area of elbow joint they perform longitudinal undulating incision with length of 12–14 cm. The top of one of the «waves» section should be turned laterally and placed 1.5–2 cm laterally from the apex of the medial epicondyle of the humerus. After transposition of the nerve in the forearm fascia in the longitudinal direction they perform C-shaped incision that form and location coincides with the peak of the «wave» of skin incision. In the area of the top «wave» they impose 3–4 vertical mattress skin and subcutaneous fascial sutures. Postoperative immobilization is not used except stitching of damaged nerve when they impose splint in flexion position of the forearm. Transpositioned nerve is held in place due to skin-subcutaneous-fascial scar created. The outcomes were assessed in 10 patients after 13 months in average (from 3 to 24) after surgery. In none patients during active-passive flexion-extension of elbow there were not determined any dislocation of the fixed ulnar nerve in the area of the ulnar groove. Full function in elbow was preserved in all of 10 patients. There was no observed any phenomena of irritation of displaced ulnar nerve by postoperative scar. The positive outcomes were obtained in all cases. Conclusions: The described by us simple and low-impact method is effective and can be successfully used to fix the ulnar nerve after itssubcutaneous transposition.